الصمود النفسي وعلاقته بالاستقرار الأسري لدى أمهات أطفال التوحد بمدينة زليتن (Journal of Humanitarian and Applied Sciences, 2023)
Abstract:The aim of the study was to find out the level of psychological resilience and its relation to family stability in the mothers of autistic children in the city of Zliten. The researcher used the descriptive approach. The study sample consisted of (34) mothers of autistic children. The study concluded that there is a high level of psychological resilience among the mothers of autistic children in Zliten. The study revealed that the mothers of autistic children in Zliten enjoy a high level of family stability. In addition, the study results confirmed that there is a moderately direct relationship between family stability and psychological resilience of autistic children mothers. In other words, the psychological resilience of autistic children's mothers has a positive (moderate) effect in achieving family stability for mothers.